Faculty members' perspectives on the influence of their students’ motivation to learn on their academic performance - AL-Tkhayneh, Khawlah Mitib; Khaled, Ahmed; Jaradat, Maram Salah; Ibrahim, Mona Kamal; Alshamsi, Issa Salim (Journal of Asian Scientific Research, 2024)
The purpose of this study is to determine how students’ motivation for learning influences faculty members' academic performance. This study employed a comparative analytical descriptive methodology to ascertain the correlation between the academic performance of faculty members and the motivation of students to learn. The study's aims and research problem defined the targeted study population consisting of faculty members from many universities in the United Arab Emirates. We obtained the data using social survey method. Snowball sampling was used to select the study sample which consisted of 130 faculty members. Calculations were made for means, standard deviations, variance testing using the ANOVA test and a Pearson correlation coefficient. The findings showed a statistically significant correlation between faculty members' performance and students' motivation. According to the experience variable, the results showed statistically significant differences in the sample members' mean scores which were attributable to the impact of students' motivation on faculty members' performance. The findings showed that faculty members' performance is enhanced by the motivation of their students to learn. The recommendations stemming from this study advocate for several key actions to improve academic performance and foster a conducive learning environment. An important recommendation among them is the implementation of faculty-specific training programs regularly. One of the most important of these recommendations is the call for the implementation of regular training courses tailored for faculty members.